A novel device to visualize Descemet membrane during donor preparation for Descemet membrane endothelial keratoplasty - Fogla, Rajesh (Indian J Ophthalmol, 2021)
The aim of this study was to describe a novel device for improved visualization of descemet membrane (DM) during donor preparation for descemet membrane endothelial keratoplasty (DMEK). Comparative analysis was performed using this device (group 1) versus conventional technique (group 2) between an experienced and a trainee surgeon. A total of 20 eyes were analyzed in each group. Average time for DM peeling by experienced surgeon was 238.8 + 17.2 s in group 1 and 382.8 + 36.3 s in group 2 (P < 0.0001), and for trainee surgeon it was 519 + 30.8 s and 686.8 + 31.9 s (P < 0.0001). Retro-illumination made it easier to identify the peripheral cut edge of DM and abnormal adhesions to the underlying stroma during peeling. In group 2, DM tear occurred in 2/10 eyes with an experienced surgeon and 4/10 eyes with a trainee surgeon. Our novel device with retro-illumination allows DM peeling for donor preparation in DMEK to be performed safely with reduced risk of tissue damage.